MicroRNA-196b Inhibits Cell Growth and Metastasis of Lung Cancer Cells by Targeting Runx2 - Xiaoxue Bai (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Lung cancer is one of the most common causes of cancer related deaths worldwide. The role of several microRNAs (miRNAs) including miR-196b in different cancers has already been established. The study was aimed to explore the role of miR-196b in lung cancer and its possible underlying mechanism. Methods: Human lung cancer cell line A549 was transfected with miR-196b mimic, miR-196b inhibitor and corresponding controls. Then cell viability, migration, invasion, and apoptosis of A549 lung cancer cells either with overexpression or with suppression of miR-196b were estimated sequentially. Next, dual luciferase activity assay was performed to clarify whether Runx2 was a direct target of miR-196b. Finally, the expressions of main factors associated with epithelial mesenchymal transition (EMT), PI3K/AKT/GSK3β, Smad, and JNK pathways were detected by western blot. Results: MiR-196b expression was significantly decreased in A549, H1650 and H1299 cell lines compared with in WI-38 and HEL-1 cell lines. Overexpression of miR-196b suppressed cell viability, migration, invasion, and induced apoptosis as well as inhibited TGF-β induced EMT process in A549 cells. In addition, Runx2 was a putative target of miR-196b, and Runx2 silence remarkably increased cell apoptosis and abolished the promotive effects of miR-196b suppression on cell viability, migration and invasion. Finally, miR-196b also mediated its action by inactivation of PI3K/AKT/GSK3β, Smad, and JNK pathways by down-regulation of Runx2. Conclusion: MiR-196b functions as a tumor suppressor that inhibited cell growth and metastasis of lung cancer cells by targeting Runx2. These findings provided further evidences for treatment of lung cancer.